Auxotypes and serogroups of penicillinase producing and non-producing strains of Neisseria gonorrhoeae isolated in Franceville, Gabon. Issue 2 (April 1985) - Yvert, F; Frost, E; Guibourdenche, M; Riou, J Y; Ivanoff, B
Abstract : The auxotypes and serogroups of 250 consecutive isolates of Neisseria gonorrhoeae from Franceville, Gabon, including 33 penicillinase producing (PPNG) strains, were identified and the results tabulated for four periods. The PPNG and certain non-PPNG strains were isolated in clusters against a relatively stable pattern of non-PPNG biotypes. Most of the non-PPNG strains were non-requiring or proline requiring strains of serogroup WII or non-requiring strains that could not be grouped with commercially available antisera. No strain requiring arginine, hypoxanthine, and uracil was observed. The PPNG strains were all serogroup WI or ungroupable and non-requiring or proline or arginine dependent auxotypes. Only one non-PPNG strain required proline or arginine and was not serogroup WII.